UPAYA PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA MELALUI PENERAPAN MODEL PEMBELAJARAN KEPALA BERNOMOR STRUKTUR - Helma Mustika; Devi Mei Riska (Universitas Islam Sumatera Utara, 2019)
Abstract. This study aims to improve students' mathematical problem-solving abilities by applying the learning model with head numbered structure. This type of research is the Class Action Research (CAR). Data collection techniques used were tests and observations. The instruments used were the problem-solving ability test, observation sheet and data analysis techniques using the problem-solving indicator values. Based on the results of the problem-solving ability test that on indicator 1 that fulfills the completeness of learning in the first cycle 63%, and the second cycle 78%. Indicator 2 in cycle I 59%, and cycle 2 70%. Indicator 3 in cycle I as 52% and cycle II is 67%. Indicator 4 in cycle I 48%, and cycle II 63%. So it can be concluded that the students' mathematical problem-solving abilities increase through the application of the learning model with head numbered structure. Key words: Head Number Structure, Problem Solving